VEGETATIVE GROWTH RATE TEST OF BOUGENVILE CUTTING AGAINST PLANT GROWTH REGULATION (PGR) AND MANURE APLLICATION IN POLYBAG - Sahrul Romadona; Cik Zulia; Safruddin Safruddin (Universitas Asahan, 2018)
This research was conducted in Mentimun Street, Siumbut Baru Village, Kisaran Timur Subdistrict, Asahan Regency, North Sumatera Province. Study time from March to May 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is PGR with 4 levels: Z0 = without PGR, Z1 = Rootone F (2 g / l water), Z2 = Atonik (2 ml / l water) and Z3 = Hantu (2 ml / l water). The second factor is by giving the ratio of manure with 4 levels ie K0 = 1: 0 (1 part of soil + 0 parts of manure), K1 = 1: 1 (1 part of soil + 1 part manure), K2 = 2: 1 (2 part of soil + 1 part manure) and K3 = 3: 1 (3 parts of soil + 1 part manure). The results showed that the best treatment of PGR was obtained at PGR Rootone F which resulted in plant height 26,36 cm, leaf number 13,71 strand, stem diameter 5,29 mm, total live crop 3,75 crop. The treatment of manure on planting medium with aratio of 2: 1 (soil: manure) is the best treatment that produce plant height 25.09 cm, the number of leaves 13.54 pieces, stem diameter 5.25 mm, the number of plants live 3.67 plants. Interaction between PGR and manure had no significant effect on all observed variables.